PENERAPAN MODEL PBL BERBANTUAN MEDIA DIORAMA TATA SURYA UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA - Khoirudin, Kukuh; Rulviana, Vivi; Retnowati, Andriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to improve science learning outcomes through the PBL model with solar system diorama media for sixth grade students of SDN 02 Winongo, Madiun City. This study is a classroom action research (CAR) conducted in 2 cycles. The subjects in this study were 9 sixth grade students. The results of the study showed that at the pre-action stage, the average student score was only 62.22 and the percentage of completion was only 44.44%. At the cycle 1 stage, the average student score increased to 72.22. The percentage of learning completion in students also increased to 88.88%. At the cycle 2 stage, the results of reflection and evaluation showed that the average student score also increased again, namely an average score of 85 and the percentage of completion had reached 100%.